O NBD como instrumento de fortalecimento da cooperação financeira do BRICS: uma análise institucional e operacional - Silva, Adynaer Geraldo Maia da (2022)
BRICS became themselves a conglomerate to question the international order, however, without opposing it. As a result of the group's sixth meeting, the New Development Bank was institutionalized to be a political-financial representation of the BRICS within the international scene, and responsible for formalizing the main characteristic, once questioned by the member countries: how increased access to credits, how long it takes to process and approve credit concession - by fixing some conditionalities and access investment for development of sustainable infrastructure, regardless the bureaucratic aspect. This research seeks to understand the New Development Bank (NBD) as a tool for enhancing the existing financial maintenance among BRICS members. Through a documentary financial investigation, the research goes through an understanding of international institutions in the context of multilateral institutions, in order to understand the role of the NDB in this regard. The supporting analysis of theoretical-conceptual studies with a neo-institutional approach is complemented by emerging studies of the role of powers in international relations. We went through three main environments where it was possible to verify the performance of the BRICS: 1) through the involvement with other international organizations (IMF, WB, UN), permeating the internal paths of insertion and representation; 2) the development of a mirror-paradigm, that is a reflection of the existing international order - more evident when the focus is intra-group cooperation and, finally, 3) a bureaucratic-institutional analysis of the NBD - with a focus on documents and reports of the bank that currently propose strategies - of perpetuating and consolidating the NBD and of actions in a financial niche do not explore as a complement to the international order. We highlight formal details, relevance, public relevance, formal details, and financial production on the bureaucratic nature of the relevant and internal aspects. The research was based on documentary analysis of financial and governance reports of the main financial entities, bibliographic support, and opinions of experts on the subject, - in total there are three opinions of Brazilian doctors on the subject. As a result, the dynamics of the world order are factors that form a representation of the BRICS in the international scenario, an alternative conglomerate to the current order that achieved a context of influence of the members in the global political international scenario.